EVALUATION ON THE SEED GERMINATION RATE OF ASHOKA (SARACA ASOCA (ROXB.) DE WILDE) WITH SPECIAL REFERENCE TO VRIKSHAYURVEDA (International Journal of Ayurveda and Pharma Research, 2016)
Ashoka (Saraca asoca (Roxb.) de Wilde) is one of the most auspicious plant mainly for females belonging to family Fabaceae. The stem bark is the widely used in several Ayurvedic preparations such as Ashokarishta which is prescribed in leucorrhoea, haematuria, menorrhagia and other gynecological disorders. It is getting â€œendangeredâ€ due to over exploitation and enormous use of its bark. Because of destructive means of extraction and the absence of an organized cultivation programs, the availability of the crude drug is diminishing and this has resulted in substitution and adulteration. It affects the Good Manufacturing Practices and resulting in deprived quality of the product which leads to hamper its efficacy. Subsequently it is a need of hour, to cultivate it in large extent, which is getting deprived because of its slow growth rate, seed dormancy and low germination rate. The present study was conducted to overcome this problem with the help of one of the method described in Vrikshayurveda.In this study, seed germination of Ashoka is carried out by three different methods i.e., conventional method, H2SO4 method and Vrikshayurveda method. Out of which Germination rate of Ashoka seeds was maximum (38%) with conventional method minimum (6%) with Vrikshayurveda method and (24%) with H2SO4 treatment. In view of observations, methods like conventional and H2SO4are more effective than the Vrikshayurveda for good germination of seeds of Ashoka. The low germination rate in Vrikshayurveda may be due to the limited description of methodology described in Vrikshayurveda with respect to quantity of cow milk, cow dung, honey, and Vidanga powder and time period for soaking seeds in cow milk, rubbing of cow dung and application of Vidanga and honey with respect to procedure. It should be studied in detail so as to get scientific insight of ancient methods of Vrikshayurveda, may prove its important with respect to maximum germination rate and healthy growth of plants.